Rate dependent behaviour and dynamic strain localisation of three novel impact resilient titanium alloys: Experiments and modelling - Zhang, L; Gour, G; Petrinic, N; Pellegrino, A (Elsevier, 2019)
The tensile behaviour of three ductile titanium alloys, Ti0.7Al4V, Ti1Al4V and Ti3Al2.5V, conceived for impact containment applications, is characterised at quasi-static, intermediate and high strain rates. Tests have been performed using a screw driven mechanical system and a bespoke in-house developed split Hopkinson tension bar equipped with ultra-high speed photographic equipment. The three alloys present noticeable strain rate sensitivity. Ti1Al4V is characterised by the lowest flow stress and highest ductility of the three alloys. Ti3Al2.5V higher flow stress but lowest strain to failure while Ti0.7Al4V has similar flow stress but larger engineering failure strain compared to Ti3Al2.5V. The dynamic true strain rate, determined by measuring the time history of the minimum cross-section diameter during necking, reaches values up to one order of magnitude higher than the nominal strain rate. This phenomenon, occurring during dynamic strain localisation, is of fundamental importance for understanding and modelling the dynamic behaviour of ductile alloys designed to withstand impact loading. The experimental results are used to determine the material parameters of the Johnson-Cook (JC) and Khan–Huang–Liang (KHL) models, which are incorporated in the ABAQUS/explicit code for finite element simulations of the dynamic tensile tests. It is found that the KHL model predicts the experimentally measured strain field, deformed geometry, effective strain rate and macroscopic force-displacement response during the high strain rate experiments with significantly better agreement than the JC model.